Source-controlled OpenFlow data plane - Zhe WANG; Man-gui LIANG; Xiao-meng JI; MateusAbisai Fillipus (Tongxin xuebao)
An OpenFlow switch typically used TCAM to speed up flow table matching. Therefore it brought problems with scale, high cost and energy consumption. To resolve these issues, a novel model called the source-controlled Open-Flow(SCOF)was proposed. SCOF used a source routing address named vector address (VA) as the switching label of the packet. VA defined the communication path. The core of SCOF data plane is vector switch. It can accomplish the data forwarding process relying only on VA, instead of flow table matching. SCOF overcomes scale problem by reducing the complexity of switch hardware and simplifying the process of updating flow table.